2006
DOI: 10.7249/cf219
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Theory of Intelligence: Workshop Report

Abstract: The RAND Corporation is a nonprofit research organization providing objective analysis and effective solutions that address the challenges facing the public and private sectors around the world. RAND's publications do not necessarily reflect the opinions of its research clients and sponsors. R ® is a registered trademark.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…A search of available literature revealed that no theory has been accepted as a definitive explanation of the process by which a national security intelligence enterprise informs decision making (Treverton et al 2006). Typically, the overall process of identifying the intelligence needs of decision-makers and carrying out the operations required to meet these needs is described in terms of a conceptual framework known as the "intelligence cycle" (Johnson 2012).…”
Section: Case Study Of the Us National Security Intelligence Enterprimentioning
confidence: 99%
“…A search of available literature revealed that no theory has been accepted as a definitive explanation of the process by which a national security intelligence enterprise informs decision making (Treverton et al 2006). Typically, the overall process of identifying the intelligence needs of decision-makers and carrying out the operations required to meet these needs is described in terms of a conceptual framework known as the "intelligence cycle" (Johnson 2012).…”
Section: Case Study Of the Us National Security Intelligence Enterprimentioning
confidence: 99%
“…They instead draw upon well-publicised hypothetical constructs which fuel current academic debate on broader intelligence and doctrinal issues espoused by Barger, 10 Chambliss 11 and Treverton. 12 There is also a deliberate attempt to avoid comparisons with civilian intelligence practices, as this work is bounded in a wholly military context. Nonetheless, such parameters do allow consideration of alternative perspectives to those found in Hulnick's original argument.…”
mentioning
confidence: 99%
“…At the completion of the analysis, analysts are required to generate reports or other products that summarize their judgments (Tenet 1999: Waltz 2003Treverton 2001Treverton , 2009Treverton and Gabbard 2008;Treverton et al 2006). In essence, the analyst's charge is "the application of human judgment to reach conclusion from a combination of evidence and assumptions" (Thomas and Cook 2005, p. 6).…”
Section: Challenges Of Data Analysismentioning
confidence: 99%
“…Central to many has been the drive to improve data collection and data analytic capabilities (Larson et al 2008;Treverton 2009;Treverton and Gabbard 2008;Treverton et al 2006).…”
mentioning
confidence: 99%